PECULIARITIES OF PREFIXAL DERIVATIVES IN LANGUAGE LEVELS. - Niyatova, Maftuna (Журнал иностранных языков и лингвистики, 2021)
The article deals with the nominative and structural-semantic features of prefixal derivatives in linguistics. The main purpose of the paper is to give further information about the history and development of prefixes, their nominative and semantic features and derivatives from prefixes, their utilization, researches done by scientists and scholars and how and which ways the derivative come into existence and examples based on them in English and so on. This paper provides detailed suggestions with illustrations, introduction, background of previous researches, methods used by scientists for finding out the foundations, results of them and conclusion section. The authors and the researchers with all levels of experience may find useful ideas in the paper.